A conceptual model of intention to adopt BYOD among HCP in Pakistan - Nisar, Saima; Sheik Osman, Wan Rozaini (2016)
Healthcare facilities and manpower in Pakistan are a generally acute shortage, incompetent. congested and overburden which cannot meet the requirements of the people visiting these facilities. Medical sectors are progressively looking for portable solutions to meet their Information Technology (IT) needs.To identify Healthcare Professionals (HCP) intention in both adopting the Bring Your Own Device (BYOD) and concerns related to security and privacy of their devices, the researchers propose a conceptual model by integrating the Consumer Acceptance and Use of Information Technology Extending the Unified Theory of Acceptance and Use of Technology (UTAUT2) and Protection Motivation Theory (PMT) which would impact their behavior intention in both using the device and provide the good understanding of concerns about security and privacy of their devices.